EXPERIMENTAL STUDY AND COMPUTATIONAL SIMULATIONAL ON THE RESISTIVITY ANSISOTROPY OF METAL AND SEMICONDUCTOR SINGLE CRYSTALS - Toshpulatov Ogabek , son of Ulugbek (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2026)
Electrical resistivity anisotropy in metal and semiconductor single crystals is an important research subject in the fields of materials science and electronics. This phenomenon is related to crystal symmetry and electron dispersion, reflecting differences in electron flow along various crystallographic directions. Experimental studies, particularly the four-point probe technique, Hall effect measurements, and magnetotransport methods, are used to measure direction-dependent resistivity in single crystals. In addition, computer modeling methods—such as Density Functional Theory (DFT), molecular dynamics, and tight-binding models—make it possible to determine electron density, phonon scattering, and transport processes. Modern approaches combine experimental results with theoretical models to predict anisotropic properties in metals and semiconductors and to design new nanoelectronic devices. The research findings have practical significance in the study of electron transport mechanisms, high-precision semiconductors, and nanoelectronic devices. This article briefly analyzes the current state and methodological approaches to studying electrical resistivity anisotropy in single crystals.